Biochemical composition and energy value of Crassostrea gigas (Thunberg) cultured in the bay of Marennes-Oleron - Deslous-paoli, Jean-marc; Heral, Maurice (EDP Sciences, 1988)
In the bay of Marennes-Oleron the dry flesh of Crassostrea gigas ranged from 29 to 52% proteins, 10 to 23% ash, 6 to 20% lipids and 0 to 4% carbohydrates of which 48.3 ± 21.6% were glycogen. The energy value ranged from 18.84 to 23.47 joule. Mg(-1) ash free dry weight (mean 20.27 J. mg(-1). Reproductive effort varied from 17.8 to 55.9% dry weight for males, and 43.1 to 61.9% for females during the first and third year of reproduction respectively. A high energy value for female gametes (23.47 to 26.24 J. mg(-1) dry tissue) was mainly due to a higher level of lipids (17.3 to 23% of dry tissue) in female gametes as compared to that in male gametes (5.9 to 12.3% of dry tissue). During the period of mass-loss which began in October and finished in March, the poor trophic conditionsof the environment resulted in the use of 74.6% of glycogen, 44% of lipids and 36% of proteins tomeet more than 50% of the requirements for basal metabolism. Dans le bassin de Marennes-Oléron, les constituants de la chair sèche des huîtres Crassostrea gigas fluctuent saisonnièrement de 29 à 52 % pour les protéines, 10 à 23 % pour les cendres, 6 à 20 % pour les lipides et 0 à 4% pour les glucides, dont 48,3 ± 21,6 % sont formés de glycogène. La valeur énergétique est comprise entre 18,84 et 23,47 joule. mg- 1 de chair sèche sans cendre (moyenne de 20,27 J.mg(- 1). L'effort de reproduction varie de 17,8 % à 55,9 % du poids sec pour les mâles, et, de 43,1% à 61,9% pour les femelles pour respectivement leur première et troisième année de reproduction. La forte valeur énergétique des produits émis par les femelles (23,47 à 26,24 J. mg (-1) de tissu sec) est induite par une plus forte teneur en lipides des gamètes femelles (17,3 à 25 % de tissu sec) que des gamètes mâles (5,9 à 12,3 % de tissu sec). Pendant la période d'amaigrissement qui débute au mois d'octobre et se termine au mois de mars, les mauvaises conditions trophiques nécessitent l'utilisation de 74,6 % du glycogène, 44 % des lipides et 36 % des protéines pour assurer plus de 50 % ...